(untitled) (Research, Society and Development, 2022)
The growth in the use of radiographic films generates a large number of them, which in most cases are not stored, collected and treated correctly, which can cause damage to the environment and health. The presence of silver and lead elements in its composition can contaminate soils and groundwater, intoxicating animals and being absorbed by plants, which can then be ingested by humans. Thus, it is important to invest in technologies that will reduce the generation of waste, in addition to the correct management of disused materials. The general objective of this research was to evaluate the knowledge of radiographic films and their packaging in three associations of residents of the Rural Zone of Governador Mangabeira-BA. This is an exploratory, educational and qualitative research of a descriptive character, with the participation of 90 members of the three resident associations studied. Semi-structured interviews were applied by means of questionnaires and the data were tabulated and analyzed by descriptive statistics using SPSS Software in version 22. It was found that 71% of the members of the associations know a radiographic film and with respect to the packaging 97% inform that they keep at home after the medical consultation for an indefinite period, confirming that there is a lack of information on how to dispose correctly. It is concluded that the implementation of the protocol for cleaning and reusing radiographic films will contribute to the improvement of economic, social and cultural impacts, directly influencing the prevention of human health and avoiding lead contamination in the environment.